Identificación especifica del agente causal de la mazorca negra (Phytophthora spp.) En cacao en la zona central del litoral. - Carranza Menéndez, Gabriela Margarita (2015)
This work was done in the laboratory of Microbiology at the State Technical University of Quevedo; the research aims to determine the species or species of Phytophthora associated with black, cob present in the central cocoa in Ecuador. The collection of ears with the disease Phytophthora spp. It was held in different farms in the central area of the coast, for isolation of the organism, ears, washed with water and then dried them later to extract small pieces of diseased tissue and placed in Petri dishes containing culture medium based on Potato Dextrose-Agar (PDA) and V8 agar, these boxes were kept in incubation until the appearance of the organism in the culture medium; 48 hours uncontaminated colonies were selected and allowed to incubate for 7 days in darkness and kept in an incubator at 26 ° C. With the aid of a Vernier calliper, two perpendicular measurements of the colony every 24 hours until full coverage of the plate is performed. Besides the appearance of the colony, these boxes are evaluated permanent mounts were also made with lactophenol + trypan blue, and the microscopic measurement of sporangia (um) its presence or absence, the length of the stalk, the type of disc was made, chlamydospore. The results obtained in this research support the hypothesis that if there is more than one species of Phytophthora associated with black pod disease.